DIESTER-CALIX[4]ARENEDIQUINONE COMPLEXATION AND ELECTROCHEMICAL RECOGNITION OF GROUP-1 AND GROUP-2, AMMONIUM AND ALKYL AMMONIUM GUEST CATIONS - Beer, P; Chen, Z; Gale, P (1994)
The synthesis, metal, ammonium and alkyl ammonium cation coordination chemistry and electrochemical recognition studies of a new diester-calix[4]arenediquinone receptor are described. © 1994.